Analysis of the Education Budgeting Process at Private Elementary SchoolSanta Lusia Sei Rotan, Medan, Indonesia - Ester; Eka Daryanto; Restu (RADINKA JAYA UTAMA PUBLISHER, PADANG< INDONESIA, 2023)
This research aims to analyze the education budgeting process at SDS Santa Lusia Sei Rotan. The type of research used in this research is descriptive research with a qualitative approach. The subject of this research is SDS Santa Lusia, while the object of this research is the education budgeting process. Determining priorities in using funds obtained by schools refers to the 8 National Education Standards (SNP) issued by the government, in the Government Regulation of the Republic of Indonesia Number 19 of 2005 concerning National Education Standards, these standards include: (1) Graduation Competency Standards; (2) Content Standards; (3) Process Standards; (4) Assessment Standards; (5) Standards for Educators and Education Personnel; (6) Infrastructure Standards; (7) Management Standards; (8) Financing Standards. Through meetings or discussions, the group responsible for each standard is determined. The process of preparing the School Activity Plan and Budget (RKAS) for SDS Santa Lusia Sei Rotam is by the initial planning. Where the chart stages have been sequenced and the implementation process can also be completed well. All parties responsible for the 8 standards also carry out their duties by a mutually agreed process.